MeTooMS: Sexual, physical, and emotional abuse experience among women with multiple sclerosis. (February 2023) - Pol-Patil, Jeta; Glanz, Bonnie; Safar, Laura; Misasi, Elizabeth; Manieri, Maria Claudia; Shanahan, Rachel; Healy, Brian; Houtchens, Maria
Background: Sexual and physical violence against disabled individuals is widespread and linked to negative public health and social outcomes. The real-world prevalence of abuse in women with multiple sclerosis (MS) has not been well studied. Objectives: To explore abuse prevalence in a real-world cohort of females with MS attending an academic MS Center. Methods: Prospective and retrospective abuse data were confidentially collected during neurology clinic visits and extracted from medical records for women attending an academic MS Center. Self-reported and provider-documented prevalence of abuse experiences were correlated with socio-economic and disease-specific factors. Results: In total, 200 women completed prospective questionnaires, and 121 non-overlapping independent health records were retrospectively reviewed. Mean age ( SD ) was 49.055 (11.39). Seventy-six (38%) reported lifetime abuse incidents; 15% were abused within the previous year. Intimate partners were the most likely verbal ( p ⩽ 0.01)) and physical ( p = 0.04) abuse perpetrators. Neurologic disability correlated with greater likelihood of verbal abuse ( p = 0.021) in prospective cohort. There was no billing or encounter documentation for any form of abuse. Conclusion: Intimate partner violence is common in women with MS, correlates with neurologic disability, and is underreported by the health system. Future research needs to focus on abuse detection and mitigation strategies.